Electronic Distraction in the Operating Room: A Major Safety Issue - Saran, Jagroop; Papadakos, Peter (Operating Room Nurses Association of Canada Journal, 2018)
The past decade has seen an increase in the use and availability of electronic devices, including computers and personal electronic devices, in the health care setting. Hospitals have invested significantly in electronic medical records and ensuring the availability of Wi-Fi and cellular networks throughout their institution. It remains to be seen if this increased accessibility has led to improved patient safety, or reduced medical errors, but it has led to a new, unanticipated, problem which may impact patient safety and professionalism. The operating room (OR) is a complex and rapidly changing environment with high cognitive load tasks requiring teamwork and communication between team members and technology. Distractions, no matter how minor, have the possibility of causing errors which could result in patient harm. In this brief review the authors discuss potential sources of distractions in the operating room, explore some methods that have addressed this issue, and outline ways to limit electronic distractions.